The Impact of the Talkies on Scottish Cinema Architecture. Issue 3 (2nd September 2019) - Peter, Bruce
Abstract : The consequences of the introduction of sound for the architecture of cinema buildings is considered with a focus upon examples in Scotland completed in the 1929–30 period. The influence of the building acoustics pioneer, Hope Bagenal, in the design of the New Victoria cinema in London and its consequences for subsequent cinemas in Scotland, designed by Alister G. MacDonald (1898–1993), David Stokes (1908–90) and James McKissack (1875–1940) is explained and contextualized. Their clean-lined and fashionable styling was not only more easily adapted for good sound reproduction but also signified that cinema as a medium was entering a new phase.